2012
DOI: 10.1093/jnci/djs179
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Lung Cancer Among Never, Former, and Current Smokers

Abstract: Our results suggest that a higher BMI is associated with a reduced risk of lung cancer in current and former smokers. Our inability to attribute the inverse association between BMI and the risk of lung cancer to residual confounding by smoking or to bias suggests the need for considering other explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
107
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 40 publications
12
107
2
2
Order By: Relevance
“…3,6,8,16 One of these studies, by contrast with the rest also reported that obese men had an increased risk of adenocarcinoma, particularly among never and former smokers. 3 Most of these studies, including ours, were limited in that there were too few cases of some histologic subtypes, especially among never smokers, to stratify analyses by smoking.…”
Section: Epidemiologymentioning
confidence: 96%
See 3 more Smart Citations
“…3,6,8,16 One of these studies, by contrast with the rest also reported that obese men had an increased risk of adenocarcinoma, particularly among never and former smokers. 3 Most of these studies, including ours, were limited in that there were too few cases of some histologic subtypes, especially among never smokers, to stratify analyses by smoking.…”
Section: Epidemiologymentioning
confidence: 96%
“…16 Using data from a large prospective study that included 9,437 lung cancer cases (415 cases among never smokers), the authors reported that BMI was more strongly associated with reductions in lung cancer risk among obese women compared with obese men. Based on this finding and the recognized strong correlations between obesity and higher levels of estrogens, 50 the authors suggest that estrogens play a role in these associations.…”
Section: True Etiological Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…As smoking status is the most common confounder in the study of the association between BMI and lung cancer risk, we noticed that the sample size was reduced a lot after focusing on nonsmokers in most original studies, in such case the error could not be avoided. It is a good advice to take a more comprehensive approach to represent life time smoking behavior in the future study as suggested by Dr. Mariam El-Zein.Recently, we noticed that Smith et al 4 also found an inverse association between BMI and lung cancer risk in smokers in a large cohort study, along with Tarnaud's findings, 5 the inverse relationship in smokers is certain and confirmable to some extent, so our extrapolated suggestion that ''smokers should improve their nutritional status and maintain a suitable body weight'' is tenable and apprehensible. However, the relationship between BMI and lung cancer risk in nonsmokers is still ambiguous, especially in males, we speculate that even such relationship exists, the extent is relatively weak, and obviously there is no evidence that obesity can increase lung cancer risk like some other types of cancer in nonsmokers.…”
mentioning
confidence: 65%